The Rise of Indonesian Communism - McVey, Ruth T. (Cornell University Press, 2019)
The Indonesian Communist Party (PKI) is the strongest political party in Indonesia. It is also the most powerful communist party outside the Sino-Soviet bloc. The oldest major Indonesian party, it was the first communist movement in Asia beyond the borders of the former Russian Empire.In The Rise of Indonesian Communism, Ruth T. McVey traces the development of the PKI from its birth in 1914 to its temporary eclipse in 1927 after a disastrous attempt at revolution. The author gives equal emphasis to the PKI' s role in Indonesian politics and its part in the international communist movement. Three aspects of domestic Indonesian communism are considered: the party's history, its place in the constellation of Indonesian political movements, and its influence on colonial government policy. The treatment provides insight into the economic, social, and political factors shaping the revolutionary movement, the significance of ideology as a motivating force in Indonesian political action, and the relationship between communism and Islam.The product of research in five countries and as many languages, Miss McVey's book is the definitive study of the beginnings of the Indonesian Communist Party. It will be vital reading for anyone interested in Indonesian politics and in the development of communism in Asia.